2016
DOI: 10.1364/oe.24.025832
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of solar noise impact on the performance of underwater wireless optical communication links

Abstract: We investigate the effect of environmental noise, caused by solar radiations under water, on the performance of underwater wireless optical communication (UWOC) systems. Presenting an analytical and generic model for this noise, we examine its impact on the link performance in terms of the bit error rate (BER). This study is conducted for different photo-detector types in the aim of highlighting practical limitations of establishing UWOC links in the presence of subsea solar noise. We show how the solar noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…Although we neglected the effect of background noise, it can severely affect the Rx performance due to the high sensitivity of SiPMs. In a recent study [39], the impact of solar background noise on the link performance was investigated for a worst-case scenario, i.e., sun at the zenith and the Rx plan directed towards the sea surface, this way, capturing the maximum solar irradiation [30]. It was shown that for the case of clear ocean waters and considering OOK modulation and the MicroSB-30020 SiPM model, for operation depths (with respect to the Rx) larger than ∼ 250 m the link performance is not practically affected by the background noise [39].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we neglected the effect of background noise, it can severely affect the Rx performance due to the high sensitivity of SiPMs. In a recent study [39], the impact of solar background noise on the link performance was investigated for a worst-case scenario, i.e., sun at the zenith and the Rx plan directed towards the sea surface, this way, capturing the maximum solar irradiation [30]. It was shown that for the case of clear ocean waters and considering OOK modulation and the MicroSB-30020 SiPM model, for operation depths (with respect to the Rx) larger than ∼ 250 m the link performance is not practically affected by the background noise [39].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It can be easily verified that in practice the variance of the Rx thermal noise is several orders of magnitude smaller than the signal amplitude and it can be neglected, compared to quantum noise. We further assume that our system operates in relatively deep waters so that we can neglect the effect of background illumination [30]. Thus, the dominant source of receiver noise is assumed to be quantum in nature.…”
Section: Link Model and Main Assumptionsmentioning
confidence: 99%
“…Two cases of clear ocean (Jerlov I) and turbid coastal waters (Jerlov 5) are considered, as for the experimental tests. The diffuse attenuation coefficient [21] for these water types is 0.08 and 0.5 m -1 , respectively. These confirm the previously presented experimental results.…”
Section: Numerical Simulation Resultsmentioning
confidence: 93%
“…where P t is the total emitted power at the Tx, φ ∈ [0, π/2] denotes the angle of irradiance, and m stands for the Lambertian order, given by m = − ln(2)/ ln(cos(φ 1/2 )), with φ 1/2 being the Tx semi-angle at half-power. We model the optical power loss by an exponential decay model, which is suitable for the case of using an LED at the Tx, see [7]- [10]. This way, assuming perfect Tx-Rx alignment and negligible turbulence effect, the captured power P Rx at the Rx is given by:…”
Section: Main Assumptions and System Modelmentioning
confidence: 99%
“…where Z is the link distance, A is the photo-sensitive area of the SiPM, and K denotes the diffuse attenuation coefficient [10]. We further neglect the effect of pulse broadening (i.e.…”
Section: Main Assumptions and System Modelmentioning
confidence: 99%